Disfunção do trato urinário inferior em doentes com esclerose múltipla - Sandra Raquel Salgado Sousa (2018)
Introduction: Multiple sclerosis is the most common chronic neurological disorder in young adults, affecting more females than males. The clinical presentation shows several autonomic disorders, but it is the symptoms of the lower urinary tract that are most commonly described by patients at the beginning of the course of the disease. Thus, it is crucial to identify the urinary symptoms so that a therapeutic plan can be decided in a timely manner in order to improve patients' quality of life and avoid urological complications. Objectives: Elucidate the pathophysiology of urinary symptoms in patients with multiple sclerosis and the respective therapeutic measures for the different types of bladder dysfunction. Development: The mechanisms underlying the micturition reflex are described and how the different locations of the lesions in the central nervous system control the clinical condition of the patient, referring to the urinary symptoms. We provide some guidelines to help in the diagnosis of urinary symptoms based on urodynamic tests. Finally, we present the various therapeutic plans that cover behavioral and pharmacological measures, alternative therapies and neural modulation, and lastly the viable surgical options to be offered to patients with multiple sclerosis. Conclusions: The symptoms of the lower urinary tract are the most common autonomic disorder in patients with multiple sclerosis. We conclude that there is a correlation between the region of the neurological lesion and the urinary symptoms presented by these patients. In the early phase this demyelinating pathology, urinary urgency is the most prevalent symptom, but at a later stage the obstructive symptoms begin to appear. This clinical picture should be early diagnosed based on urodynamic tests, in order to elaborate a personalized therapeutic plan to each type of bladder dysfunction. However, there are refractory patients to the first lines of treatment, which force to rise to more invasive measures.